Family Harmony in Contemporary Islamic Law: Ibn ‘Āshūr’s Maqāṣid Perspective on Marital Rights and Duties - Muhamad Zaenal Muttaqin; Ahmad Ibrizul Izzi; Reza Fauzi Nazar; Shohibul Wafa Tadzul Arifin; Muhamad Yogi Sandra (MILRev: Metro Islamic Law Review, 2026)
This study critically examines Ibn ‘Āshūr’s interpretation of the maqāṣid al-shari’ah and its potential to strengthen harmonious family values in contemporary Muslim societies, with a particular focus on Indonesia. Using a qualitative, descriptive-analytical approach, the research examines Ibn ‘Āshūr’s key writings alongside classical and modern commentaries to provide a comprehensive understanding of his framework. To ensure practical relevance, the study incorporates illustrative examples drawn from jurisprudential sources and current socio-legal realities that shape Muslim family life today. The findings show that Ibn ‘Āshūr’s emphasis on preserving religion, life, intellect, lineage, and wealth provides a strong normative basis for addressing central issues in Islamic Family Law, such as spousal rights, gender equity, and child custody. His prioritization of justice, moral development, and public welfare underscores that legal interpretation should serve broader ethical objectives rather than rigid textualism alone. However, when applied to modern socio-cultural contexts, several challenges emerge. Evolving gender roles, diverse family structures, and socioeconomic disparities often require adaptations beyond Ibn ‘Āshūr’s original formulations. These realities call for a contextualized reading of maqāṣid to maintain its relevance and effectiveness in contemporary settings. This study’s academic contribution lies in bridging classical maqāṣid theory with the concrete needs of modern Islamic Family Law reform. By positioning Ibn ‘Āshūr’s ideas alongside those of contemporary scholars, the research clarifies where his framework remains robust and where it requires reinterpretation. This integrative approach offers a fresh analytical lens for understanding family-related legal issues, combining normative principles with socio-legal awareness.